Approaching the lithium-manganese oxides' energy storage limit with Li2MnO3 nanorods for high-performance supercapacitor. (January 2018) - Xu, Weina; Jiang, Zhiqiang; Yang, Qi; Huo, Wangchen; Javed, Muhammad Sufyan; Li, Yanrong; Huang, Li; Gu, Xiao; Hu, Chenguo
Abstract: Lithium manganese oxides are of great interest due to their high theoretical specific capacity for electrochemical energy storage. However, it is still a big challenge to approach its large theoretical limit. In this work, we report that Li2 MnO3 nanorods with layered structure as superior performance electrode for supercapacitors. The synthesized Li2 MnO3 nanorods possess large specific surface area of 179.5 m 2 /g. The electrode made of the as-obtained Li2 MnO3 nanorods exhibits high specific capacitance of 1129.5 F/g at 2 mV/s in 3 M LiCl electrolyte. Detailed electrochemical analysis shows that diffusion controlled processes contribute most of the relative capacity. First-principles calculations within density functional theory also show that the diffusion of Li + ions in the lithium layer is much easier than that in the manganese-lithium-oxygen layer. Therefore, the ion flow in lithium layer provides most of the high specific capacitance during charge/discharge. A flexible symmetric supercapacitor is assembled based on Li2 MnO3 /carbon fabric cloth. Such device demonstrates high specific capacitance, high energy density, high power density and excellent cycling stability. Three supercapacitors in series can efficiently power 288 blue LEDs in parallel for about 11 min. These results indicate that Li2 MnO3 nanorods are very promising as super electrode material for supercapacitors. Graphical abstract: Highlights: Li2 MnO3 nanorods have a large specific surface area of 179.5 m 2 /g and exhibit an outstanding specific capacitance of 1129.5 F/g. The diffusion mechanism of lithium ions in Li2 MnO3 is investigated based on the theoretical calculation. Three flexible symmetric supercapacitors in series could effectively power about 288 blue LEDs for about 11 min.